2016
DOI: 10.21837/pmjournal.v1.i1.38
|View full text |Cite
|
Sign up to set email alerts
|

The Suburbanisation of the Kuala Lumpur Metropolitan Region

Abstract: The Klang Valley has been experiencing rapid urbanisation especially during the past two decades. The area has expanded to become a larger entity known as the Kuala Lumpur Metropolitan Region (KLMR). But this development comes at the expense of Kuala Lumpur. The city had consistently recorded net-out migration during the period. This development has consequences on the urban fabric of the city and can lead to the problem

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Most of the interviewees hardly able to brief (even rough estimation) agreeable percentages; except that citing zakat's amount (2.5% from the prescribed zakat formula3 F § ) as their bases. Likewise, zakat is only imposed to the shareholders' fund since the paid-up capital provided by them, if there is surplus (Abdullah et al 2012). A simple comparison between takaful operators and conventional insurers will signify that in term of contribution to the nation in forms of taxes -takaful operator contributes more due to zakat payment (pseudo religious tax) and corporate tax compared to conventional insurers, albeit in term of amount the latter might contribute more.…”
Section: Findings1 F †mentioning
confidence: 99%
“…Most of the interviewees hardly able to brief (even rough estimation) agreeable percentages; except that citing zakat's amount (2.5% from the prescribed zakat formula3 F § ) as their bases. Likewise, zakat is only imposed to the shareholders' fund since the paid-up capital provided by them, if there is surplus (Abdullah et al 2012). A simple comparison between takaful operators and conventional insurers will signify that in term of contribution to the nation in forms of taxes -takaful operator contributes more due to zakat payment (pseudo religious tax) and corporate tax compared to conventional insurers, albeit in term of amount the latter might contribute more.…”
Section: Findings1 F †mentioning
confidence: 99%
“…In Malaysia, studies on the issues of urban growth and land use, sustainable urban development, urban planning and conservation had long used traditional regression approach (e.g. Abdullah, 2003;Jaafar, 2004;Rainis & Noresah, 2004;Tahir & Roe, 2006;Samat, 2007;Lee, Lim, & Nor'Aini, 2008;Osman et al, 2008;Tan, Lim, MatJafri, & Abdullah 2009). On the other hand, studies which used GWR include modelling urban spatial structure Noresah and Rainis, (2009), analyzing land use change (Noresah, Gairola, & Talib, 2010), assessing the rental value of shop houses (Eboy, Ibrahim, & Buang, 2006) and examining the locational attributes effect on residential property values (Dziauddin & Idris, 2017).…”
Section: Problem Statementmentioning
confidence: 99%
“…Malaysia is experiencing rapid urbanization resulting from population increase and in-migration to urban areas (Abdullah, 2003). Recent projections indicated that the urbanization process in Malaysia would result in urban population exceeding 65 percent by the year 2020 (Government of Malaysia, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another example is a parallel language corpus as a resource for Malay language reported by [2] and a basic tokenizer tool for Jawi writing reported by [3]. The Malay language is categorised as an agglutinative or derivative language where most of the words are formed by merging affixes with root words [4][5]. Affixation is performed by adding the affix at the beginning (prefixes), middle (infixes) or at both the ends (circumfixes) of the root word.…”
Section: Introductionmentioning
confidence: 99%